PERMODELAN PERGERAKAN TANAH PADA LERENG - Daniel, Hartanto (Seri Kajian Ilmiah, 2013)
Soil movement often occur on the slopes natural or embankment. In the absence of natural slopes non vegetation cover and slopes with vegetation cover became the main object of this research. Rate is the final results obtained from laboratory scale experiment of the natural slopes of the approach. Slope Angle is very influential to the movement rate of the soil. Angle of tilt 20ï° generating rate of land between: 15 cm/sec up to 66 cm/sec for compacted soil and 100 cm/sec for non compacted soil. While the angle of 40 ï° yield rate of the ground between: 100 cm/sec to 125 cm /sec for compacted soil and rate between : 85 cm/sec to 200 cm/sec for non compacted soil.